REVOLUSI MENTAL APARATUR SIPIL NEGARA DALAM MEWUJUDKAN TATA PEMERINTAHAN YANG BAIK DAN BERSIH - Anggoro, Firna Novi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Corruption practices continue to occur in Indonesia and most of them are carried out by the State Civil Apparatus (ASN). Even though the bureaucratic reform program has been running, corrupt bureaucratic behavior still occurs. Efforts to build ASN that are clean from corrupt practices are carried out through a mental revolution. Changes in the ASN mindset and work culture (culture set) are very important in realizing good and clean governance. ASN's self-perception, attitudes and behavior need to be changed immediately because it often traps ASN in corrupt behavior. The mental revolution movement needs to be pursued immediately in the hope that values ??that are implemented continuously will form a new culture. Efforts to be taken in changing mentality are carried out through continuous education, training, and supervision. In order for the implementation of the mental revolution to run effectively, it also needs to be accompanied by the consistent application of a reward and punishment system so as to be able to motivate and raise awareness for all ASN of the importance of a mental revolution. This mental revolution campaign needs to be carried out on an ongoing basis by using various means of communication that are expected to reach all government institutions and all levels of society